Sintesis Metil Ester sebagai Biodiesel Minyak Biji Kesambi (Schleichera oleosa L.) melalui Esterifikasi dan Transesterifikasi - Lailatusholihah, Isna; Suganda, Angga; Mahardika, Micha; Prastiwi, Dina Alva; Situmeang, Boima (Universitas Papua, Manokwari, Indonesia, 2024)
Synthesis of methyl ester as biodiesel kesambi seed oil (schleichera oleosa l.) through esterification and transesterification has been successfully conducted. Kesambi seeds are one of the seeds that can produce essential oils, which is about 70%. The methods used in this study are esterification and transesterification. Characterization of methyl ester compound used H-NMR spectrometry The procedure was sample preparation, degumming, esterification, transesterification, and biodiesel quality test. The esterification process had been two steps using a methanol ratio of 20: 1. The biodiesel quality test results are not sufficient from the SNI 04-7182: 2006 standard, where the acid number is 0.718 Mg KOH / g, moisture content 0.32-0.51%, density 840 kg / m3 and viscosity 25.1 Mm2 / s.